A Review of Teachers and Teaching On Stage and On Screen: Dramatic Depictions - Mortimer, Amy (Art/Research International)

(untitled) (University of Alberta, 2023)
This piece is a review of Teachers and Teaching on Stage and on Screen: Dramatic Depictions, edited by Diane Conrad and Monica Prendergast (2019). Mortimer’s personal poetic response opens the review to honour her artistic ways of knowing and responding to the content. The book’s contributing authors, all educators, provide diverse cultural, social, and socio-economic perspectives and insights into how teachers and teaching are represented in film and on stage. Conrad and Prendergast’s book invites a range of audiences (from pre-service teachers to academics) to reflect on dramatic depictions of teachers and to use them to deepen understandings of the complexities of teaching, schooling, and students—and, if readers are teachers themselves, to examine their own practice.